The digital revolution in Asia and its macroeconomic effects - Tahsin Saadi Sedik; Sally Chen; Tarhan Feyzioglu; Manuk Ghazanchyan; Souvik Gupta; Sarwat Jahan; Juan Manuel Jauregui; Tidiane Kinda; Vipichbolreach Long; Elena Loukoianova; Alexandros Thomas Mourmouras; Masahiro Nozaki; et al. (Asian Development Bank Institute (ADBI), 2019)
Asia is at the forefront of the digital revolution, which promises a radical transformation of the global economy, and indeed of society itself, while at the same time threatening substantial disruptions and dislocation. For instance, workers worry that robots will make them obsolete, while financial supervisors are concerned about the risks to financial stability posed by the latest fintech innovations. At the same time, digitalization may well be a key driver of productivity growth and improved welfare. This paper focuses on whether the digital revolution in Asia is driving growth or disrupting it. Given the diversity of digital innovations and the sparsity of data, the paper uses a multipronged approach to analyze the digital economy in Asia.
Keywords: G21; MI3; O33; 330; fintech; digital innovations